Synthesis and Characterization of β‐Cyclodextrin Nanosponge and Its Application for the Removal of p‐Nitrophenol from Water. Issue 10 (13th September 2017) - Salgın, Sema; Salgın, Uğur; Vatansever, Özgün
Abstract : β‐Cyclodextrin (β‐CD)‐based nanosponges (NSs) were synthesized by reacting β‐CD with hexamethylenediisocyanate (HMDI) as the cross‐linking agent. The effects of the reaction parameters, such as the β‐CD/HMDI molar ratio, reaction temperature, and type of cross‐linker, on the NS synthesis were systematically examined. The removal of p ‐nitrophenol ( p ‐NP) from water by NSs was determined through adsorption experiments. The adsorption efficiency of the NSs synthesized at different temperatures did not change significantly, but the adsorption efficiency of the NSs was influenced by the HDMI concentration and cross‐linker type. The characteristic Fourier transform infrared (FTIR) bands showed that p ‐NP was adsorbed parallel to the surface of the NSs. The Langmuir model had the highest correlation coefficient for the adsorption of p ‐NP onto the NSs. The maximum adsorption capacity ( Q °) and adsorption energy ( b ) for p ‐NP were estimated to be 1.0 mg g −1 and 1.837 L mg −1, respectively. The NSs synthesized under the optimum conditions were characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), X‐ray diffraction (XRD), thermogravimetric analysis (TGA), and laser diffraction particle size (LDPS) analysis. The combination of the results from SEM, TEM, and LDPS analysis indicated that the synthesized NSs had a porous, sponge‐like, and rigid structure. The results of XRD and TGA also revealed the formation of β‐CD‐NSs. Abstract : The effects of reaction parameters on nanosponge (NS) synthesis are systematically analyzed. To determine the optimal synthesis conditions, the adsorption efficiencies of NSs are determined for the removal of p ‐nitrophenol ( p ‐NP) from aqueous solutions. The synthesized porous and sponge‐like NS exhibits high adsorption capacity and short adsorption time toward p ‐NP.